Personal branding for librarians: The way forward - Syed Ahmad Alhady, Syed Mohammed Alhady; Zakaria, Azfahanee Zakaria (2010)
Librarians have always been labelled as knowledge gatekeepers and persons who ‘shusshhh’ people around. However, that may be true years and decades ago. Going forward, do we librarians want to be labelled as such? A brand is a promise delivered. It is our reputation and legacy. Branding is a practice of producing trust which when we market our services, we do so with a promise to meet or exit the expectation of the customer. Academicians talk and discuss the importance of personal branding with fellow students all the time. However some students are just too sceptical to agree and follow the path and information which have been identified for them. Many students are unaware that personal branding does not happen overnight. It takes quite a while for a person to have a personal brand which would suit a person and does not look fake on him or her. This paper discusses the importance of personal branding for all future librarians and how it would assist them to succeed in the challenging working world. It also discuses on how UiTM would create and mould its outstanding future librarians.